مولانا عمر دینپوری کی شاعری میں وحدانیت کا رنگ: Religious Thoughts of Muhammad U. Deenpori’s Brahui Poetry - Rodeni, Yousaf Ali (Al-Burz, 2012)
This research article describes a vital point in Brahui poetry. This portion of Brahui literature has several factualness. Ordinary, synthetic, social, tribal, epic, revolutionary, and religious topics have been versified. This article shows the religious thoughts of Muhammad U. Deenpori which is well known personality of Durkhani school of thought. The core theme of this article is too aware the readers and public that today’s religious scholar, learned and Mulla, Syed are reflecting the face of religion it is fact and tactless. The follower of above subjected scholar is caused to produce illiteracy in the community.